Praktik Paronan Pemeliharaan Sapi Perspektif Sosiologi Hukum Islam - Bintang Ayu Puspita Sari Edi Saputri; Siti Nurhayati (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2021)
There were various ways of raising cattle between capital and calves. There were 4 (four) types of capital sharing between cattle owners and custodians, while the calf paring method consists of 2 (two) types. The transfer of capital (cows) does not mention the amount of capital (cow price). There was no written agreement regarding the agreement in raising cattle, everything was done orally. In addition, there was no time limit in the practice of raising cattle in Purworejo Village and there was no specific benchmark regarding the percentage of Paronan. Second, the sociological perspective of Islamic law on the practice of raising cattle in Purworejo Village, Kandat District, Kediri Regency can be seen from several aspects. There were factors behind the community doing Paronan namely economic factors, educational factors, socio-cultural factors. All agreements were made orally, if there was a written agreement it was considered unreasonable. The function of AGIL (Adaption, Goal Attainment, Integration and Latency) can run properly so that it caused a balance in the social system that occurs in Purworejo Village